2015
DOI: 10.7439/ijbr.v6i3.1650
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fasting lipid profile and glycated hemoglobin in obese subjects at university of calabar teaching hospital, Nigeria

Abstract: Background:Obesity is a major public health issue which has been established to be a significant risk factor for several metabolic disorders such as impaired glucose tolerance, dyslipidaemia, and atherosclerosis. This study aimed to evaluate and compare the serum lipid profiles and glycatedhaemoglobin of obese and non-obese adults in Calabar, Nigeria. Methodology:This was a prospective comparative study that involved quantifying serum lipid profile and glycated hemoglobin (HB1Ac) in seventy (70) obese subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…They found that WHR was not significantly associated with abnormal lipid parameters in both male and female with T2DM [12]. Besides Indian authors similar studies have been conducted in other nations too [12,13,14,15]. Only one of the aforementioned correlations between anthropometric parameters and parameters of the lipid profile of T2DM patients was in line with some of our findings, namely "HDL-cholesterol correlated negatively with BMI" [12].…”
Section: Resultssupporting
confidence: 85%
“…They found that WHR was not significantly associated with abnormal lipid parameters in both male and female with T2DM [12]. Besides Indian authors similar studies have been conducted in other nations too [12,13,14,15]. Only one of the aforementioned correlations between anthropometric parameters and parameters of the lipid profile of T2DM patients was in line with some of our findings, namely "HDL-cholesterol correlated negatively with BMI" [12].…”
Section: Resultssupporting
confidence: 85%